Improving the Resilience of SD-WAN Networks Operating over GEO Satellite Links using Adaptive Tunneling - Janusz DUDCZYK; Mateusz SERGIEL; Jaroslaw KRYGIER (Communications of International Proceedings, 2026)
This paper summarizes an adaptive SD-WAN tunneling mechanism designed for underlays based on geostationary (GEO) satellite links. The proposed solution operates entirely in IP-based tunneling and combines adaptive segmentation, controlled packet duplication, and receiver-side duplicate elimination to mitigate typical transmission impairments of GEO SATCOM links. Experimental results obtained in a prepared testbed show that our mechanism fully eliminates packet loss and unmanaged duplication under extreme latency and loss conditions, transforming an unstable satellite underlay into a predictable and deterministic transport channel suitable for SD-WAN deployments.
Keywords: SD-WAN; tunneling mechanism; satellite networks; packet loss mitigation